Protesting the United States Olympic Committee - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows Santa Clara University law students picketing the soccer trials at Stanford University. A demonstrator, possibly Melinda Walton, holds signs that read, "The USOC is suing the Gay Games for $96,000 for the use of the word "Olympic" while "Special Olympics", "Firemen's Olympics" remain unharrassed" and "Where are your Olympic donations going? To sue the Gay Games for $96,000!!!"